A History of Icelandic Literature - Einarsson, Stefán (Johns Hopkins University Press, 1957)
Stefán Einarsson covers almost a thousand years of Icelandic literature in tracing the influence of the sagas and eddic poems. The book begins with background on Icelandic literature, outlining its literary roots in Scandinavia. Following this, Einarsson provides a thorough survey of Icelandic literature through the 1950s.